PENGARUH PROFITABILITAS, FINANCIAL LEVERAGE, ASSET EFFICIENCY, DAN KEBIJAKAN DEVIDEN TERHADAP SUSTAINABLE GROWTH RATE PADA PERUSAHAAN YANG TERCATAT DALAM JAKARTA ISLAMIC INDEX (JII) PERIODE 2021-2023 - Yulia, Rizka; Rahayu, Sri; Elviani, Sri; Rahmarisa, Faty (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to examine the effect of profitability, financial leverage, asset efficiency, and dividend policy on the sustainable growth rate (SGR) of companies listed on the Jakarta Islamic Index (JII) for the period 2021–2023. A quantitative research approach was employed, utilizing secondary data obtained from companies’ annual financial reports. The sample was selected using purposive sampling, resulting in 15 companies out of 30 listed on the JII that met the predetermined criteria. Data analysis was conducted using multiple linear regression with the aid of SPSS version 25. The results of the study indicate that, partially, profitability as proxied by Return on Equity (ROE) and financial leverage as proxied by Debt to Equity Ratio (DER) have a positive and significant influence on SGR. In contrast, asset efficiency as measured by Total Asset Turnover (TATO) and dividend policy as measured by Dividend Payout Ratio (DPR) have a negative and significant effect on SGR. Simultaneously, all four independent variables exert a statistically significant influence on the sustainable growth rate